Environment and economic development in the Eastern Caribbean. - Simmons, David A. (1992)
Points out that economic growth and sustained development are the dominant concerns of economic planners, and environmental deterioration is one of the factors that can lead to an interruption of economic growth. Notes that the transition from current development practices to productive patterns based on the concept of sustainable development is one of the greatest challenges facing the region.